Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) dalam Pembelajaran IPA untuk Meningkatkan Pemahaman Keanekaragaman Makhluk Hidup dan Lingkungan pada Siswa SD Negeri 1 Bambel - Aanzar Mizana Nugraha; Suyit Ratno (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to explain the implementation of the Pancasila Student Profile Strengthening Project (P5) in science teaching to improve students' understanding of the diversity of living things and the environment at SD Negeri 1 Bambel. The methodology used was a descriptive qualitative approach with data collection through observation, interviews, and documentation. The research findings indicate that the implementation of P5 for the Sustainable Lifestyle theme took place in a planned manner through environmental observation activities, data collection on organisms, classification of living things, and the creation of campaign media for environmental awareness. Student participation increased significantly, as evidenced by their enthusiasm in group work and project presentations. The learning evaluation also showed an increase in understanding of science concepts, from an average pre-test score of 67.5 to 80.2 in the post-test. In addition to cognitive improvements, the P5 project also strengthened students' character in aspects of critical thinking, creativity, cooperation, communication, and environmental awareness. Some challenges faced included time management and differences in ability among students. Overall, the implementation of P5 in science teaching proved effective in developing students' conceptual understanding and character comprehensively.